James Jacobs, The First Battle of El Alamein, 1-30 July 1942: A South African Perspective (Historia, 2021)
The majority of academic and popular studies on the South African participation in the Second World War continue to focus on the varied offensive deployments of the Union Defence Force to the operational theatres in East Africa, North Africa, Madagascar and Italy. As of late there is somewhat of a renewed drive to study the South African participation in the war from a more general war and society approach, where the prime focus is on such diverse topics as the individual experience of war, the SouthAfrican home front, prisoners of war, demobilisation, and various medical aspects to name but a few. Despite this renewed drive to study the South African participation from a far broader perspective, the mainstay of professional and amateur historianscontinue to focus on key events surrounding the Union Defence Force deployments to North Africa and Italy in particular. Of these, the South African reverses at Sidi Rezegh and Tobruk continue to receive the bulk of the attention, mainly due to the immense impact these reverses held for the Union at a political, societal and military level. Moreover, the fact that nearly 14,000 South African soldiers were captured during these battles continue to overshadow the vital role that Union Defence Force troops played during the remainder of the campaign in the Western Desert.
Keywords: James Jacobs; El Alamein; North Africa; East Africa; Second World War